KINERJA BONGKAR MUAT CONTAINER PADA DERMAGA SELATAN TERMINAL OPERASI II PT PELABUHAN TANJUNG PRIOK TAHUN 2016 - Muh. Kadarisman; Karina Martha Ramadhani; Tjetjep Karsafman (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of this research is to analyze the relation between idle time and performance of containers’ loading and unloading activities at South Pier of Terminal II Tanjung Priok Port in 2016. Located in North Jakarta, Tanjung Priok Port is the busiest port in Indonesia. This port deals with more than 30% of Indonesia's non-oil and gas commodities, and about 50% of all goods flow in and out of Indonesia through this port. Therefore, Tanjung Priok Port becomes  an economic barometer of Indonesia.. To solve the problems, researchers used 2 methods; they were field data method (field research) and data library (library research). Simple linear regressionanalysis used t-test with consideration and determination. The result of this research shows that there is a strong relationship between idle time and performance of containers’ loading and unloadingactivities , (Y = 7,775 + 0,496X). The result value of r is  77.4% which means there is a strong and positive relationship between idle time variable and containers’ loading and unloading performance. The determinant coefficient of R² is 59.8%, and other determinant is about 40.2%.